Сучасна Браїла (Румунія) і колишні запорожці: історична пам’ять і залишки топографії - Бачинська, О.; Мацюк, Д. (Чорноморська минувшина, 2013)
У статті йдеться про перебування в місті-фортеці Браїла задунайських запорожців на початку ХІХ ст. З’ясовано відображення цих подій в писемних джерелах та відсутність даних про них у музеях та сайті сучасного міста Браїла. На сьогодні свідками історичних подій початку ХІХ ст., в яких брали участь козаки, залишились мечеть на території колишньої фортеці, що перетворена на православний храм Святих Архангелів Михаїла та Гавріїла (Biserica «Sfinţii Arhangheli Mihail şi Gavril»), забудова сучасного міста за топографією фортеці та узбережжя Дунаю. The article is devoted in the fortress city of Braila Transdanubian Cossacks at the beginning of the XIX century. It was revealed the level of reflection of these events to the stay in the written sources and the lack of data of Ukrainian Cossack- Zaporozhian in the museum and at the website of the modern city of Braila. It is shown that the Cossacks were a part of Transdanubia garrison (from a thousand to three thousand people) during the Russian -Turkish war of 1806-1812 under the direct supervision of Kish ataman Ignat Koval and commandant of the fortress Ahmet Pasha. In Braila during 1806-1809 years Cossacks Kish was siturated. After the fort was occupied by Russian troops, the Cossacks, crossed to the Russian army, and part of them continued service in the Ottoman army. Today the witnesses of historic events of the XIX century, connected with the Cossacks, remained a mosque in the former fortress, which turned into the Orthodox Church of the Holy Archangels Michael and Gabriel (Biserica "Sfinţii Arhangheli Mihail şi Gavril"), development of the modern city according to the topography of fortress and the coast of Danube. We hope our small publication will advance the study of Ukrainian Cossacks stay in Braila by Romanian researchers, and later this new conclusions will appear in historical information about this wonderful city. Статья посвящена пребыванию в городе-крепости Браила задунайских запорожцев в начале XIX в. Выяснено отображение этих событий в письменных источниках и отсутствие данных об украинских казаках-запорожцах в музее и сайте современного города Браила. Показано, что задунайские запорожцы составляли часть гарнизона крепости (от тысячи до трех тысяч человек) в во время русско-турецкой войны 1806-1812 гг. под непосредственным руководством кошового отамана Игната Коваля и коменданта крепости Ахмет-паши. В Браиле на протяжении 1806-1809 гг. находился Кош запорожцев. После того, как крепость была занята русскими войсками, часть казаков перешла в российскую армию, а часть продолжила службу в армии Османской империи. Сегодня свидетелями исторических событий начала XIX в., в которых принимали участие казаки, остались мечеть на территории бывшей крепости, которая превращена в православных храм Святых Архангелов Михаила и Гавриила (Biserica «Sfinţii Arhangheli Mihail şi Gavril»), застройка современного города по топографии крепости и побережье Дуная. Надеемся, наша небольшая публикация станет толчком к изучению пребывания украинского казачества в Браиле со стороны румынских исследователей, что впоследствии отразится в исторических справках об этом замечательном городе.